Oncology palliative care in a public home-care service - Pilatti, Patrícia (2017)
Objective: To identify the profile of palliative care oncology patients and their multidisciplinary needs in a home-care service. Method: A cross-sectional study with secondary data collection from cancer patients in palliative care, attended by the Home-Care Program of Conceição Hospital Group in 2013. Approved by the Ethics and Research Committee under No. 13,203. Results: There were 63 home-care patients diagnosed with cancer. Among those, 71.5% (n=45) were in palliative care, and 15.5% (n=7) had more than one admission to the Program. The median follow-up time of all patients was 22 (3-146) days, while for the number of home visits it was 6 (1-34). In addition to weekly home visits, patients were assisted by a nutritionist, a physiotherapist, and a social worker. Concerning the 45 hospitalizations, their main demands were pain management, wound dressings, glycemic control and intravenous antibiotic therapy. The main clinical complication was the reintroduction of a nasoenteral catheter (n=5). Discharge in stable health conditions occurred in 10 patients. Clinical complications and outcomes were analyzed. Conclusion: This study allowed us to identify the main demands of oncological palliative care patients attended by one Home-Care Service. We observed that most patients needed complex care, but the healthcare staff and/or trained caregiver were still able to provide it.